2020
DOI: 10.1186/s12887-020-1910-z
|View full text |Cite
|
Sign up to set email alerts
|

Are parental dietary patterns associated with children’s overweight and obesity in China?

Abstract: Background: It is believed that parents have a great influence on their children's dietary behaviours. However, it is not clear whether parental food patterns are associated with children's nutritional status in China, which includes a vast territory with rich, diverse cultures. The goal of this project is to systematically study the associations between parental food intake and children's overweight and obesity in China, according to children's ages and regional differences. Methods: Based on individual food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…Maternal high-quality diet was not associated with risk of obesity in offspring aged 9-14 years in mother-child pair studies conducted in the United States [47]. However, parental food intake was highly correlated with Chinese children and adolescent's food intake, although this association between parental food intake and offspring's overweight and obese was most significant in 7-12-year-old children compared to 13-18-year-old adolescents [48]. In New Zealand, higher parental diet quality was associated with lower consumption frequency of confectionary, chocolate, cakes, biscuits, and savory snacks in 9-11-year-old children [49].…”
Section: Discussionmentioning
confidence: 87%
“…Maternal high-quality diet was not associated with risk of obesity in offspring aged 9-14 years in mother-child pair studies conducted in the United States [47]. However, parental food intake was highly correlated with Chinese children and adolescent's food intake, although this association between parental food intake and offspring's overweight and obese was most significant in 7-12-year-old children compared to 13-18-year-old adolescents [48]. In New Zealand, higher parental diet quality was associated with lower consumption frequency of confectionary, chocolate, cakes, biscuits, and savory snacks in 9-11-year-old children [49].…”
Section: Discussionmentioning
confidence: 87%
“…Parents have to monitor their children's food intake and ensure they are eating healthy diet. In addition, parents should practice healthy dietary habits because parental food intakes are highly correlated with their children's food intakes especially among young children (Tang et al, 2020). Parents also have great impacts on their children's eating behaviors (Patel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that parents’ eating habits and food preferences play an important role in shaping food intake patterns in children [ 5 ] as children consider their parents as role models. Previous studies suggested that parents who are “healthy role models” would be more likely to have children who consume healthier foods [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%